ANALISIS NOVEL “BUMI MANUSIA” KARYA PRAMOEDYA ANANTA TOER: KAJIAN SEMIOTIKA ROLAND BARTHES (ANALYSIS OF THE NOVEL “BUMI MANUSIA” BY PRAMOEDYA ANANTA TOER: ROLAND BARTHES SEMIOTICS STUDY) - Noor Hanifah (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
Analysis of the novel "Bumi Manusia" by Pramoedya Ananta Toer: A Semiotic Study of Roland Barthes. This study aims to describe the meaning of denotation, connotation and myth in the text of the novel Bumi Manusia by Pramoedya Ananta Toer. The method used is descriptive and the approach used is the semiotic approach. Data analysis techniques with content analysis. The results showed that each data analyzed contained denotation, connotation and myth based on the concept of Roland Barthes. The conclusion from this research is the text in the novel Bumi Manusia by Pramoedya Ananta Toer, that myths are discourses that were believed during the time when the discourse was circulating, the findings that the researchers found were closely related to the meaning of connotations in the text. The meaning of denotation contained in the novel Bumi Manusia is that it describes the condition of the Indonesian people during the Dutch East Indies colonial period, politics, the ideology of the people at that time. The meaning of connotations in the analysis of the novel Bumi Manusia is a social allusion to the injustices experienced by the natives.Key words: semiotics, Roland Barthes, novel, denotation, connotationAnalisis Novel “Bumi Manusia” karya Pramoedya Ananta Toer: Kajian Semiotika Roland Barthes. Penelitian ini bertujuan mendeskripsikan makna denotasi, makna konotasi dan mitos dalam teks novel Bumi Manusia karya Pramoedya Ananta Toer. Metode yang digunakan yaitu deskriptif dan pendekatan yang digunakan pendekatan semiotika. Teknik analis data dengan content analysis. Hasil penelitian menunjukkan setiap data yang dianalisis terdapa makna denotasi, makna konotasi dan mitos menurut konsep Roland Barthes. Hasil simpulan dalam penelitian ini teks dalam novel Bumi Manusia karya Pramoedya Ananta Toer, bahwa mitos merupakan wacana-wacana yang dipercayai pada masa wacana itu beredar, temuan yang peneliti temukan mitos berkaitan erat dengan makna konotasi dalam teks. Makna denotasi yang terdapat dalam novel Bumi Manusia yaitu menggambarkan keadaan rakyat Indonesia pada masa penjajahan Hindia Belanda, politik, ideologi orang-orang pada masa itu. Makna konotasi yang dalam analisis novel Bumi Manusia yaitu singgungan sosial tentang ketidakadilan yang dialami Pribumi.Kata-kata Kunci: semiotika, Roland Barthes, novel, konotasi, denotasi